SISTEM INFORMASI ROUTE SHEET ORDER PADA IDA CATERING SEMARANG BERBASIS WEB MOBILE (Information Technology and Telematics, 2015)
Abstract Ida Catering is a catering business in the field of food sales for weddings, meeting, gathering, and others - others who are in the area of ​​Semarang. For the current business processes are run by Ida Catering still use traditional manual systems and where record-keeping system for mail order still use manual way to the last note is copied so it takes a long time coupled with the accuracy of order data that makes misscomunication among catering employees of the administration, marketing, kitchens and warehouses as well as the owner.The objectives to be achieved is to make the route information system applications mobile web-based order sheet at Ida Catering to increase the turnover of catering revenue due to accurate data and in accordance with the order of costomer and help the internal performance become more maximal catering minimize existing misscomunication.The results in this study is the existence of the route sheet information system applications mobile web-based order in Ida Catering Semarang can facilitate the administration if there is a change costomer orders inputted from marketing to admin, and then to the kitchen, warehouse and owner no longer take orders repeatedly with how to copy it. With a view to facilitate each department receives order information is updated. Keywords : Catering, Mobile Web-based, Route Sheet, Order and Income